ER stress protein PERK promotes inappropriate innate immune responses and pathogenesis during RSV infection. Issue 2 (18th April 2021) - Narayanan, Samanthi; Elesela, Srikanth; Rasky, Andrew J; Morris, Susan H; Kumar, Surinder; Lombard, David; Lukacs, Nicholas W
Abstract: The activation of dendritic cells (DC) during respiratory viral infections is central to directing the immune response and the pathologic outcome. In these studies, the effect of RSV infection on development of ER stress responses and the impact on innate immunity was examined. The upregulation of ER stress was closely associated with the PERK pathway through the upregulation of CHOP in RSV infected DC. The inhibition of PERK corresponded with decreased EIF2a phosphorylation but had no significant effect on Nrf2 in DC, two primary pathways regulated by PERK. Subsequent studies identified that by blocking PERK activity in infected DC an altered ER stress response and innate cytokine profile was observed with the upregulation of IFNβ and IL-12, coincident to the down regulation of IL-1β. When mitochondria respiration was assessed in PERK deficient DC there were increased dysfunctional mitochondria after RSV infection that resulted in reduced oxygen consumption rates (OCR) and ATP production indicating altered cellular metabolism. Use of a CD11c targeted genetic deleted murine model, RSV infection was characterized by reduced inflammation and diminished mucus staining as well as reduced mucus-associated gene gob5 expression. The assessment of the cytokine responses showed decreased IL-13 and IL-17 along with diminished IL-1β in the lungs of PERK deficient infected mice. When PERK-deficient animals were assessed in parallel for lung leukocyte numbers, animals displayed significantly reduced myeloid and activated CD4 and CD8 T cell numbers. Thus, the PERK activation pathway may provide a rational target for altering the severe outcome of an RSV infection through modifying immune responses. Graphical Abstract: The ER stress protein PERK induces an altered innate immune phenotype in DC that promotes a pathogenic response during RSV infection.